Asian American Student Engagement in Student Leadership and Activism. Issue 160 (20th December 2017) - Manzano, Lester J.; Poon, OiYan A.; Na, Vanessa S.
Abstract: Conceptual models for understanding the ways in which Asian American students engage in leadership and activism are interrogated. The chapter provides a discussion of implications for student affairs professionals working with Asian American student leaders and activists.